2012
DOI: 10.7575/ijalel.v.1n.4p.86
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Modality Specificity of L2 Learners’ STM Abilities in Learning Vocabulary via PDAs

Abstract: This paper is licensed under a Creative Commons Attribution 3.0 License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Nine [12], [6], [46], [47], [48], [49], [50], [51] and [52] of the 50 studies indicated that there were challenges that related to a need for identifying and using instructional design guidelines to design mobile training content. Seventeen studies [6], [53], [54], [55], [44], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], and [67] mentioned challenges related to adapting and appropriating mobile learning technology to learn in a compatible way with suitable learning theories, objectives and actual training/learning needs.…”
Section: Discussionmentioning
confidence: 99%
“…Nine [12], [6], [46], [47], [48], [49], [50], [51] and [52] of the 50 studies indicated that there were challenges that related to a need for identifying and using instructional design guidelines to design mobile training content. Seventeen studies [6], [53], [54], [55], [44], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], and [67] mentioned challenges related to adapting and appropriating mobile learning technology to learn in a compatible way with suitable learning theories, objectives and actual training/learning needs.…”
Section: Discussionmentioning
confidence: 99%